2012
DOI: 10.1007/s11999-012-2431-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Patient Expectations About Arthroplasty at Initial Presentation for Hip or Knee Pain Differ by Sex and Ethnicity?

Abstract: Background Many studies show gender and ethnic differences in healthcare utilization and outcomes. Patients' presurgical cognitions regarding surgical outcomes also may vary by gender and ethnicity and play a role in explaining utilization and outcome differences. However, it is unclear whether and to what extent gender and ethnicity play a role in patients' presurgical cognitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Although, to our knowledge, there are no previous studies involving patients with shoulder and elbow conditions for comparison, other studies with patients considering hip and knee arthroplasties have reported similar findings. Ethnic minorities have been found to be less willing to consider and proceed with total joint arthroplasties [5,9,18,19,[21][22][23] as a result of differences in expectations of the postoperative length of stay, amount of pain, and recoverable function [5,6,9,18]. Although lower levels of income and education have been associated with poorer rates of agreement to undergo invasive cardiac procedures [1], Hawker et al [15] found that income and education are not independent determinants of willingness to proceed with hip and knee arthroplasties, although patients with lower levels of income and education had a greater unmet need for total joint arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, to our knowledge, there are no previous studies involving patients with shoulder and elbow conditions for comparison, other studies with patients considering hip and knee arthroplasties have reported similar findings. Ethnic minorities have been found to be less willing to consider and proceed with total joint arthroplasties [5,9,18,19,[21][22][23] as a result of differences in expectations of the postoperative length of stay, amount of pain, and recoverable function [5,6,9,18]. Although lower levels of income and education have been associated with poorer rates of agreement to undergo invasive cardiac procedures [1], Hawker et al [15] found that income and education are not independent determinants of willingness to proceed with hip and knee arthroplasties, although patients with lower levels of income and education had a greater unmet need for total joint arthroplasties.…”
Section: Discussionmentioning
confidence: 99%
“…Lower socioeconomic status also was associated with increased perceived risks and decreased perceived success of surgery and therefore less likelihood to proceed with surgery [12]. Increasing age and female sex also have been shown to be associated with less willingness to proceed with hip and knee arthroplasties [12,19], although Hawker et al [13] reported that females were as willing as males to have surgery but were less likely to consult with a physician. The level of general physical health of the patient does not appear to significantly influence their willingness to consider surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These questionnaires consisted of between two and 45 items, most frequently querying expectations regarding factors such as residual pain, degree of mobility, activities of daily living, recreational/social activities, ability to work, and complications. One study asked patients to pick from supplied lists of potential surgical complications and activities that the patient would be able to do postoperatively [28]. All of the questionnaires were self-completed by patients on paper.…”
Section: Expectation Measures For Which Development and Validity Datamentioning
confidence: 99%
“… 2) It is known that patients are well informed about the benefits and have realistic expectations following conventional TJA. 3) However, very little is known on patients' knowledge regarding RN systems in orthopaedic surgery. Patients are becoming more resourceful in seeking information from the internet and other media; it has been established that having expectations of surgery met is the strongest predictor of the postoperative assessment of outcomes and satisfaction, even more so than optimal pain relief and the patient's hospital experience.…”
mentioning
confidence: 99%